Early intervention and prompt corrective action in Europe - David G. Mayes (Bank of Finland, 2009)
The present crisis has revealed that, as expected, much of the safety net for handling failures in the banking system is deficient, particularly for cross-border banks, and the present problems had to be handled by a range of ad hoc measures. The principal new measure that needs to be undertaken in most countries is the implementation of a satisfactory special resolution regime for banks. This paper, however, deals with two further steps that could assist the operation of the safety net. The first is to ensure earlier intervention so there is more time to put a satisfactory rescue or resolution in place. The second is to implement a regime of prompt corrective action (structured early intervention and resolution, SEIR) so that both supervisors and banks know that a regime of increasing intensity will take place according to a strict timetable that will end in the authorities stepping into the bank while it still has positive capital, if the earlier stages are not effective. The paper evaluates the means of doing this in a European environment making use of the experience in the United States. It concludes that, while a lot can be done even within the current framework of national supervision, particularly through pre-positioning, cross-border banks can be better treated either by revising the home-host responsibilities or by moving to a supranational level of responsibility for SEIR for those banks whose continued operation is considered necessary for financial stability in any member state.
URN:NBN:fi:bof-20140807240
Keywords: 330